Velhice e memória - Seabra, Renata da Costa (2009)
This is a longitudinal study using patients with light alterations in cognitive memory. The subjects used in this study where divided into two groups: Control and Test. The main goal of this study was to evaluate any improvement in the memory of patients in the Test group that received an intervention based on cognitive stimulus. It was also evaluated if subjects from the test group noticed any improvement in life quality. The relationship between depressive humor and memory or education level and memory deficits were also studied. This study was conducted in the city of Belo Horizonte. The Test group received the intervention in Hospital Belo Horizonte within the Espaço Saúde . The Control group was represented by members of the elderly group from a parish called Igreja Santíssima Trindade. Both Control and Test groups were evaluated at the beginning of the study and 6 weeks later, which was the interval for intervention in the Test group. This study was motivated by the unsystematic observation of the effect of cognitive losses in elderly and by the limited literature in this field. The results revealed a statiscally significant improvement in memory following intervention. No correlation was observed between memory and depression or education. Based on this data and the constant increase in the elderly population, we conclude that it is of utmost importance to conduct activities that focus on improving the life of elderly